Implementasi Higher Order Thinking Skills (HOTS) terhadap Hasil Belajar Siswa pada Pembelajaran MIPA - Rezeki, Sri; Fitriani, Indah; Ramadhani, Febrina (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2024)
This research aims to: 1) describe the implementation of HOTS in the learning process on student learning outcomes in Mathematics and Natural Sciences learning; and 2) describe the supporting and inhibiting factors in implementing HOTS in Mathematics and Natural Sciences learning. The method used in this research is the Systematic Literature Review method or literature study which focuses on the process of reviewing and analyzing thoroughly several pieces of literature that are appropriate to the research topic. The results of this research show that: 1) the application of HOTS in the Mathematics and Natural Sciences learning process has proven to be effective in improving student learning outcomes. This effectiveness can be seen from changes in students' cognitive aspects, where in conventional learning they tend to use low-level thinking (LOTS), while with the implementation of HOTS, they begin to develop high-level thinking abilities, such as critical, creative and evaluative thinking. These three aspects equip students with a more mature mindset, enabling them to face and solve various problems in various situations; and 2) supporting factors for HOTS implementation include teacher competency, facilities and infrastructure, classroom management and learning planning. Meanwhile, the inhibiting factors in implementing HOTS are inadequate teacher education qualifications and a relatively low level of teacher understanding regarding HOTS. Keywords: Higher Order Thinking Skills (HOTS), learning outcomes, literature review.